Entre a Arbitragem Brasileira e a Arbitragem Europeia: Um estudo acerca da Agência Nacional de Telecomunicações (ANATEL) e a Office of Comunications (OFCOM) - Achille kurtouis (International Journal of Science and Society, 2021)
A procura pela arbitragem como meio de resolução de litígios se mostra importante em função do grande volume de causas submetidas ao julgamento do Estado - juiz, em número inversamente proporcional ao preparo técnico daqueles que são investidos na função jurisdicional por ato estatal. Atualmente, falar em composição extrajudicial de conflitos no campo da regulação significa adentrar em um cenário de grandes discussões e debates. Dessa forma, o texto busca construir razões para a resolução de litígios no âmbito das telecomunicações por meio da arbitragem, inclusive, face a experiência europeia, a exemplo da OFCOM. One of the duties of the regulatory agencies is precisely the solution of conflicts between players in the sector at the administrative level. When analyzing the forms of dispute resolution in the European Union, a peculiar behavior can be highlighted. In major disputes that occur on the continent, it is more common to use arbitration than the judiciary. In fact, arbitration can be used by ANATEL as an important tool to ensure a broad, free and fair competition between providers of telecommunications services, as it dodges the slowness of the judiciary and the possibility of sham litigations, enabling the rapid adoption of a decision that often affects the rights of a great number of users of telecommunications services. The high prestige enjoyed by these methods of dispute resolution pays homage to their characteristic of being a neutral forum positioned far from a regulatory agency of a specific country and close to referees chosen by common agreement, or even connected to international institutions that provide the arbitration services in commercial disputes.